Building effective governments in developing countries: from a global goal to intelligent action (experience of Brazil) - Gazarian, Svitlana (Pressing Problems of Public Administration, 2023)
The problem of creating effective governments in developing countries within the framework of the existing global system, while protecting their sovereignty and national power, is studied. An interdisciplinary approach to the study of the topic is highlighted. It is shown that the answer to the search for objective criteria for evaluating the results of administrative activity, which would testify to its effectiveness, is currently considered to be the Good Governance concept. One of its key principles is the principle of effectiveness, which consists in achieving the maximum possible positive result in accordance with the needs of society, given the most rational use of resources. An analysis of the effectiveness of the Government of Brazil, which has undergone repeated attempts to reform public administration, has been made. However, bureaucracy still remains one of the biggest problems of the state. It was noted that in the countries of Latin America, the reforms implemented under the influence of international institutions have been yet unsuccessful due to substantial socioeconomic inequality, political instability, and institutional culture and management based on Weberian principles. It is emphasized that the key obstacle to reforms is that the need for administrative changes is not rooted in the minds of administrators and managers. The values of the ‘government effectiveness’ indicator for Brazil and Ukraine are compared. A gradual positive dynamics of Ukrainian government’s activity (as distinct from that of the Brazilian government) is noted, which is assumed to be due to cooperation with society and the implementation of European values and standards of Good Governance. The focus is laid on the possibility of applying a mixed, hybrid approach to improving governance efficiency in developing countries. Its reference point is a competent government, the effectiveness of which is enhanced by the use of information technologies of new generation (artificial intelligence, etc.), and issues of transparency and accountability are measured by the public using established parameters. It is proposed to expand the knowledge about the concept of ‘Intelligent Governance’ with the provision about the professional intelligence of officials as a lever for increasing government efficiency. It has been concluded that to ensure the effectiveness of the government in developing countries, it is important to focus on the cooperation between the authorities and the public for their general mutual benefit.